Soil and Plant Analytical Laboratory Network of Africa (SPALNA): purchasing, servicing and maintenance of scientific equipment in Africa - Adeoye, G.; Uponi, J.I. (2002)
This Soil and Plant Analytical Laboratory Network of Africa (SPALNA) has been involved in training laboratory technologists in Africa on maintenance of science equipment since 1992. We have observed a wide diversity of makes and models of scientific equipment in various laboratories. This makes a uniform approach to servicing and maintenance a bit problematic. It is suggested that standardization of analytical procedures and equipment be adopted on a regional basis. To minimize difficulties with maintenance, local development and fabrication of scientific equipment should be encouraged. Regional equipment centers should be established and staffed with trained maintenance personnel.